GENERAL SECONDARY EDUCATION IN UKRAINE IN THE CONTEXT OF EDUCATION IN OTHER EUROPEAN COUNTRIES: DURATION AND STRUCTURE - Vasyl Kremen; Oleksandr Liashenko; Olena Lokshyna (National Academy of Educational Sciences of Ukraine, 2020)
The aim of the paper is the comparative analysis of the structure of the general secondary education system in Ukraine and the education systems of thirty eight countries participating in the EU Erasmus+ Programme (27 EU Member States, as well as Albania, Bosnia and Herzegovina, Iceland, Liechtenstein, Norway, Northern Macedonia, Serbia, Turkey, Montenegro, Switzerland, United Kingdom).The authors have analysed the duration of education and the structure of an academic year in Ukraine and in other European countries and made conclusions on the compatibility of the instruction time and holidays length in the Ukrainian general secondary education institutions with those in the foreign ones. Basing on the analysis of the main development trends in the European education area countries the authors have formulated proposals to improve the instruction organisation in the Ukrainian schools in compliance with the transformations currently taking place in general secondary education in Ukraine.